The within-population variability of leaf spring and autumn phenology is influenced by temperature in temperate deciduous trees - Denéchère, Rémy; Delpierre, Nicolas; Apostol, Ecaterina Nicoleta; Berveiller, Daniel; Bonne, Fabrice; Cole, Ella; Delzon, Sylvain; Dufrêne, Eric; Gressler, Eliana; Jean, Frédéric; Lebourgeois, François; Liu, Guohua; et al. (International journal of biometeorology, 2021)
Leaf phenology is a major driver of ecosystem functioning in temperate forests and a robust indicator of climate change. Both the inter-annual and inter-population variability of leaf phenology have received much attention in the literature; in contrast, the within-population variability of leaf phenology has been far less studied. Beyond its impact on individual tree physiological processes, the within-population variability of leaf phenology can affect the estimation of the average budburst or leaf senescence dates at the population scale. Here, we monitored the progress of spring and autumn leaf phenology over 14 tree populations (9 tree species) in six European forests over the period of 2011 to 2018 (yielding 16 site-years of data for spring, 14 for autumn). We monitored 27 to 512 (with a median of 62) individuals per population. We quantified the within-population variability of leaf phenology as the standard deviation of the distribution of individual dates of budburst or leaf senescence (SD BBi and SD LSi , respectively). Given the natural variability of phenological dates occurring in our tree populations, we estimated from the data that a minimum sample size of 28 (resp. 23) individuals, are required to estimate SD BBi (resp. SD LSi ) with a precision of 3 (resp. 7) days. The within-population of leaf senescence (average SD LSi = 8.5 days) was on average two times larger than for budburst (average SD BBi = 4.0 days). We evidenced that warmer temperature during the budburst period and a late average budburst date were associated with a lower SD BBi , as a result of a quicker spread of budburst in tree populations, with a strong species effect. Regarding autumn phenology, we observed that later senescence and warm temperatures during the senescence period were linked with a high SD LSi , with a strong species effect. The shares of variance explained by our models were modest suggesting that other factors likely influence the within-population variation in leaf phenology. For instance, a detailed analysis revealed that summer temperatures were negatively correlated with a lower SD LSi .